A method for preparing medium-entropy boron carbide ceramics

Through the preparation method of medium-entropy boron carbide ceramics, the problem of difficult control of the purity of boron carbide ceramics in the prior art is solved through ball milling and multiple vacuum heat treatments, and the preparation of high purity and single-phase solid solution is achieved. It is simple to operate and is suitable for improving the relevant performance of C/C composite materials.

CN118637917BActive Publication Date: 2025-05-02ZHENGZHOU UNIV
View PDF 2 Cites -1 Cited by

Patent Information

Application Number
CN202410855428.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2025-05-02
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

The existing boron carbide ceramic preparation methods are difficult to control the purity of the product due to process problems, and the operation is complicated, making it difficult to ensure the high purity of the prepared boron carbide ceramic.

Method used

Using a preparation method of medium-entropy boron carbide ceramic, a medium-entropy (Ti1/3Zr1/3Ta1/3)ByCz boron carbide ceramic is obtained by ball milling TiO2, ZrO2, Ta2O5 and C powder, and then two vacuum heat treatments are used to obtain (Ti1/3Zr1/3Ta1/3)Cz boron carbide ceramic, and then mixed with B4C, and then formed medium-entropy (Ti1/3Zr1/3Ta1/3)ByCz boron carbide ceramic after three heat treatments.

Benefits of technology

The high purity preparation of medium-entropy boron carbide ceramics is achieved. The product is a single-phase tightly arranged hexagonal crystal structure, which is simple to operate and easy to control the reaction process, ensuring the high purity and excellent performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118637917B_ABST
    Figure CN118637917B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of carbide ceramics, and particularly to a preparation method of medium-entropy boron carbide ceramics. The method of the present invention first ball-mills and mixes TiO2, ZrO2, Ta2O5 powders with C powder, and then obtains (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )C ceramic powder after two vacuum heat treatments. Then, it is mixed with B4C and prepared into medium-entropy (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B y C z boron carbide ceramics through a borothermal reaction. Among them, #imgabs0# the method of the present invention combines the high-temperature resistance characteristics of carbides and the oxidation resistance characteristics of borides to prepare a new type of medium-entropy (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B y C z boron carbide ceramics with excellent properties. The operation is simple, fast, controllable, and the cost is low, meeting the concept of green energy conservation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbide ceramics, and in particular to a method for preparing medium-entropy borocarbide ceramics. Background Art

[0002] According to the size of the entropy value (S), materials are usually divided into low entropy (S≤1.0R), medium entropy (1.0R≤S≤1.61R) and high entropy (S≥1.61R) materials; high entropy ceramics usually refer to solid solutions formed by five or more ceramic components. Due to their unique "high entropy effect" and superior performance, they have become a hot topic in the ceramic field in recent years; similar to high entropy ceramics, through appropriate component design, medium entropy ceramics can also obtain many excellent properties, such as strong thermal stability, high hardness, ablation resistance, high temperature oxidation resistance, etc.; in addition, compared with high entropy ceramics, medium entropy ceramics have the advantages of simple components, easy control of ingredients, and easy synthesis.

[0003] There is relatively little research on medium-entropy ceramics, and its synthesis process and conditions are not yet clear; the Chinese invention patent "CN109180188A A high-entropy boron-containing carbide ultra-high temperature ceramic powder and its preparation method" discloses a method for preparing borocarbide ceramics, in which carbide ceramic powder is obtained by a single heat treatment, and then B2O3 is used as a boron source, and a carbon source is added to eliminate the influence of oxygen in B2O3; in the preparation method, it is necessary to strictly control the amount of B2O3 added and the corresponding carbon source ratio, and the purity of the obtained borocarbide ceramics is not easy to control, which brings inconvenience to the preparation.

[0004] Therefore, a preparation method that is simpler and more controllable to operate, thereby effectively ensuring the purity of the prepared borocarbide ceramics, is a problem that needs to be solved. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing medium-entropy borocarbide ceramics to solve the problem of difficult control of product purity due to process problems in the existing borocarbide ceramic preparation methods.

[0006] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing medium entropy boron carbide ceramics, comprising the following steps:

[0007] S1. Add raw material powder, zirconium oxide balls and anhydrous ethanol into a ball mill respectively, dry and sieve after ball milling to obtain a mixed powder; wherein the raw material powder contains only TiO2, ZrO2, Ta2O5 and C, and the molar amount of each metal element in the raw material powder is equal;

[0008] S2, the powder obtained in S1 is pressed into a block and placed in a graphite crucible for a primary heat treatment to obtain a ceramic block; the obtained ceramic block is crushed, ground and sieved in an agate mortar to obtain a ceramic powder; the obtained ceramic powder is placed in a graphite crucible for a secondary heat treatment to obtain (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )C carbide ceramic powder;

[0009] S3, adding the carbide ceramic powder obtained in S2, B4C and anhydrous ethanol into a ball mill respectively, drying and sieving after ball milling to obtain a mixed powder of carbide ceramic and B4C;

[0010] S4, the mixed powder obtained in S3 is pressed into a block and placed in a graphite crucible for three heat treatments to obtain (Ti 1 / 3Zr 1 / 3 Ta 1 / 3 )B y C z Boron carbide ceramic powder, prepared (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B y C z Boron carbide ceramic powder is a single-phase close-packed hexagonal crystal structure, in which: y+z=1, the five elements Ti, Zr, Ta, C, and B are evenly distributed.

[0011] Furthermore, in the S1, the molar ratio of TiO2, ZrO2, Ta2O5 and C in the raw material powder is 1:1:0.5:9.5; the particle size of each component is 1-3 μm, and the purity of each component is ≥99.9%.

[0012] Furthermore, the mass ratio of the raw material powder, zirconium oxide balls and anhydrous ethanol is 1:5:5; the ball milling time is 12 hours, the ball milling speed is 90 rpm; the drying temperature is 100° C., and the drying time is 2-3 hours.

[0013] Furthermore, in the S2, both the primary heat treatment and the secondary heat treatment are carried out in a vacuum sintering furnace, and the vacuum degree in the vacuum sintering furnace is less than 5 Pa; the temperature of the primary heat treatment is 1700°C, and the temperature of the secondary heat treatment is 2000°C.

[0014] Furthermore, the time for the primary heat treatment and the secondary heat treatment is 2 hours; after the heat treatment, the temperature is reduced to 1000° C. at a rate of 10° C. / min, and then naturally cooled to room temperature in the furnace.

[0015] Furthermore, in the S3, the mass ratio of carbide ceramic powder to B4C is 4:1; the ball milling time is 12 h, and the ball milling speed is 90 rpm.

[0016] Furthermore, in the S4, the three heat treatments are carried out in a vacuum sintering furnace, the temperature of the three heat treatments is 2000°C; the time of the three heat treatments is 2h; after the heat treatment, the temperature is reduced to 1000°C at a rate of 10°C / min, and then naturally cooled to room temperature in the furnace.

[0017] Beneficial effects of the present invention:

[0018] 1. The method of the present invention is to mix TiO2, ZrO2, Ta2O5 powders with C powder by ball milling and then perform vacuum heat treatment twice to obtain (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )C ceramic powder, and then mixed it with B4C and subjected to boron thermal reaction to obtain the medium entropy (Ti 1 / 3 Zr 1 / 3Ta 1 / 3 )B y C z Boron carbide ceramics, medium entropy (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B y C z Boron carbide ceramics are single-phase solid solutions with a close-packed hexagonal structure and high purity;

[0019] 2. The preparation method of the present invention is simple to operate, easy to control the reaction process, no impurities are introduced during the process, and is conducive to optimizing the content of each component to obtain a high-purity single-phase solid solution;

[0020] 3. Entropy (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B y C z Boron carbide ceramic powder has both the high temperature resistance of carbides and the antioxidant properties of borides, and is expected to be used as a coating material to improve the relevant properties of C / C composites. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is the X-ray diffraction spectrum of the borocarbide ceramic powder of Example 1 of the present invention;

[0022] Figure 2 This is a scanning electron microscope image of borocarbide ceramic powder of Example 1 of the present invention;

[0023] Figure 3 This is the X-ray diffraction pattern of the borocarbide ceramic powder of Comparative Example 1 of the present invention;

[0024] Figure 4 This is a scanning electron microscope image of borocarbide ceramic powder of Comparative Example 1 of the present invention;

[0025] Figure 5 This is the X-ray diffraction pattern of the borocarbide ceramic powder of Comparative Example 2 of the present invention;

[0026] Figure 6 This is the X-ray diffraction pattern of the borocarbide ceramic powder of Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0028] Example 1

[0029] The raw powders TiO2, ZrO2, Ta2O5, and C were calculated and weighed according to the stoichiometric ratio of 1:1:0.5:9.5, and their particle sizes were all 1-3 μm, and the purity was ≥99.9%. The raw powders, zirconium oxide balls, and anhydrous ethanol were then added to a ball mill in a mass ratio of 1:5:5, and the roller milling time and speed were 12 h and 90 rpm, respectively. After ball milling, the mixture was placed in an oven and dried at 100 °C for 2-3 h, and a mixed powder was obtained after sieving.

[0030] The mixed powder was pressed into a block, placed in a graphite crucible, and subjected to carbon thermal reduction reaction in a vacuum sintering furnace. The vacuum degree in the furnace was less than 5 Pa, and the temperature was raised to 1700°C for heat treatment. After keeping the temperature for 2 hours, the temperature was lowered to 1000°C at a rate of 10°C / min, and finally cooled to room temperature with the furnace.

[0031] The ceramic block was crushed and ground in an agate mortar, sieved with a 200-mesh screen, and the obtained ceramic powder was subjected to secondary heat treatment at 2000°C using the same method to finally obtain (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )C ceramic powder.

[0032] The carbide powder and B4C were mixed in a mass ratio of 4:1. The roller milling time and speed were 12 h and 90 rpm respectively. The milling medium was anhydrous ethanol. After ball milling, the mixed powder of carbide ceramic powder and B4C was obtained after drying and sieving.

[0033] The mixed powder was then pressed into a block, placed in a graphite crucible, and heated to 2000°C in a vacuum sintering furnace. After keeping the temperature for 2 hours, the temperature was reduced to 1000°C at a rate of 10°C / min and then cooled to room temperature with the furnace. (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B 2 / 3 C 1 / 3 Boron carbide ceramic powder.

[0034] Depend on Figure 1It can be seen that a single-phase (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B 2 / 3 C 1 / 3 Obvious diffraction peaks appear near 26.3°, 33.4°, 43.0°, 54.1°, 59.6°, 65.0°, 66.3°, 70.1°, 76.3° and 84.7°, and their crystal plane indices are (001), (100), (101), (002), (110), (102), (111), (200), (201) and (112), respectively; Figure 2 It can be seen that the prepared (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B 2 / 3 C 1 / 3 The borocarbide ceramic powder is a single-phase close-packed hexagonal crystal structure, and the four elements Ti, Zr, Ta, C, and B are evenly distributed with each other.

[0035] Comparative Example 1

[0036] The raw powders TiO2, ZrO2, Ta2O5, and C were calculated and weighed according to the stoichiometric ratio of 1:1:0.5:9.5, and their particle sizes were all 1-3 μm, and the purity was ≥99.9%. The raw powders, zirconium oxide balls, and anhydrous ethanol were then added to a ball mill in a mass ratio of 1:5:5, and the roller milling time and speed were 12 h and 90 rpm, respectively. After ball milling, the mixture was placed in an oven and dried at 100 °C for 2-3 h, and a mixed powder was obtained after sieving.

[0037] The mixed powder was pressed into a block, placed in a graphite crucible, and subjected to carbon thermal reduction reaction in a vacuum sintering furnace. The vacuum degree in the furnace was less than 5 Pa, and the temperature was raised to 1700°C for heat treatment. After keeping the temperature for 2 hours, the temperature was lowered to 1000°C at a rate of 10°C / min, and finally cooled to room temperature with the furnace.

[0038] The ceramic block was crushed and ground in an agate mortar, sieved with a 200-mesh screen, and the obtained ceramic powder was subjected to secondary heat treatment at 2000°C using the same method to finally obtain (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )C ceramic powder.

[0039] The carbide powder and B4C were mixed in a mass ratio of 4:1. The roller milling time and speed were 12 h and 90 rpm respectively. The milling medium was anhydrous ethanol. After ball milling, the mixed powder of carbide ceramic powder and B4C was obtained after drying and sieving.

[0040] The mixed powder was then pressed into a block, loaded into a graphite crucible, and heated to 1900°C in a vacuum sintering furnace. After keeping the temperature for 2 hours, the temperature was reduced to 1000°C at a rate of 10°C / min and then cooled to room temperature in the furnace. (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B 2 / 3 C 1 / 3 Boron carbide ceramic powder.

[0041] like Figure 3 As shown, the prepared borocarbide ceramic powder exhibits the diffraction peak of TaC, indicating that the powder is a mixture of these two substances. This indicates that during the sintering process, the temperature is too low to form a single-phase solid solution of borocarbide, and the product purity is low.

[0042] Comparative Example 2

[0043] The raw powders TiO2, ZrO2, Ta2O5, and C were calculated and weighed according to the stoichiometric ratio of 1:1:0.5:9.5, and their particle sizes were all 1-3 μm, and the purity was ≥99.9%. The raw powders, zirconium oxide balls, and anhydrous ethanol were then added to a ball mill in a mass ratio of 1:5:5, and the roller milling time and speed were 12 h and 90 rpm, respectively. After ball milling, the mixture was placed in an oven and dried at 100 °C for 2-3 h, and a mixed powder was obtained after sieving.

[0044] The mixed powder was pressed into a block, placed in a graphite crucible, and subjected to carbon thermal reduction reaction in a vacuum sintering furnace. The vacuum degree in the furnace was less than 5 Pa, and the temperature was raised to 1700°C for heat treatment. After keeping the temperature for 2 hours, the temperature was lowered to 1000°C at a rate of 10°C / min, and finally cooled to room temperature with the furnace.

[0045] The ceramic block was crushed and ground in an agate mortar, sieved with a 200-mesh screen, and the obtained ceramic powder was subjected to secondary heat treatment at 2000°C using the same method to finally obtain (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )C ceramic powder.

[0046] Carbide powder and B4C were mixed in a mass ratio of 8:1, wherein the particle size of B4C was less than 200 meshes, the roller milling time and rotation speed were 12 h and 90 rpm respectively, the milling medium was anhydrous ethanol, and after ball milling, the mixed powder of carbide ceramic powder and B4C was obtained after drying and sieving.

[0047] The mixed powder is pressed into a block, loaded into a graphite crucible, heated to 2000°C in a vacuum sintering furnace, kept warm for 2 hours, then reduced to 1000°C at a rate of 10°C / min, and then cooled to room temperature with the furnace, and the borocarbide ceramic powder is obtained.

[0048] like Figure 5 As shown, the prepared borocarbide ceramic powder exhibits diffraction peaks of ZrC, TaC, and TaB2, indicating that the powder is a mixture of these three substances. This indicates that during the sintering process, the B4C content is low and the temperature is low, and a single-phase solid solution of borocarbide cannot be formed.

[0049] Comparative Example 3

[0050] The raw powders TiO2, ZrO2, Ta2O5, and C were calculated and weighed according to the stoichiometric ratio of 1:1:0.5:9.5, and their particle sizes were all 1-3 μm, and the purity was ≥99.9%. The raw powders, zirconium oxide balls, and anhydrous ethanol were then added to a ball mill in a mass ratio of 1:5:5, and the roller milling time and speed were 12 h and 90 rpm, respectively. After ball milling, the mixture was placed in an oven and dried at 100 °C for 2-3 h, and a mixed powder was obtained after sieving.

[0051] The mixed powder was pressed into a block, placed in a graphite crucible, and subjected to carbon thermal reduction reaction in a vacuum sintering furnace. The vacuum degree in the furnace was less than 5 Pa, and the temperature was raised to 1700°C for heat treatment. After keeping the temperature for 2 hours, the temperature was lowered to 1000°C at a rate of 10°C / min, and finally cooled to room temperature with the furnace.

[0052] The ceramic block was crushed and ground in an agate mortar, sieved with a 200-mesh sieve, and the carbide powder and B4C were mixed in a mass ratio of 4:1, wherein the particle size of B4C was less than 200 mesh. The roller milling time and speed were 12 h and 90 rpm respectively, and the ball milling medium was anhydrous ethanol. After ball milling, the mixed powder of carbide ceramic powder and B4C was obtained after drying and sieving.

[0053] The mixed powder is pressed into a block, loaded into a graphite crucible, heated to 2000°C in a vacuum sintering furnace, kept warm for 2 hours, then reduced to 1000°C at a rate of 10°C / min, and then cooled to room temperature with the furnace, and the borocarbide ceramic powder is obtained.

[0054] Comparing this comparative example with Example 1, this comparative example only undergoes one heat treatment during the carbon thermal reduction reaction. Figure 6 As shown, the prepared borocarbide ceramic powder exhibits TaC, Ti 0.5 Zr 0.5 The diffraction peak of B2 indicates that the powder is a mixture of these two substances, indicating that boron carbide cannot form a single phase solid solution during the sintering process.

[0055] The present invention is not limited to the above-mentioned optimal implementation mode. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that are the same or similar to those of the present application fall within the protection scope of the present invention.

Claims

1. A method for preparing medium entropy boron carbide ceramics, characterized in that: The following steps are involved: S1. Add raw material powder, zirconium oxide balls and anhydrous ethanol into a ball mill respectively, dry and sieve after ball milling to obtain a mixed powder; wherein the raw material powder contains only TiO2, ZrO2, Ta2O5 and C, and the molar amount of each metal element in the raw material powder is equal; S2, the powder obtained in S1 is pressed into a block and placed in a graphite crucible for a primary heat treatment to obtain a ceramic block; the obtained ceramic block is crushed, ground and sieved in an agate mortar to obtain a ceramic powder; the obtained ceramic powder is placed in a graphite crucible for a secondary heat treatment to obtain (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )C carbide ceramic powder; S3, adding the carbide ceramic powder obtained in S2, B4C and anhydrous ethanol into a ball mill respectively, drying and sieving after ball milling to obtain a mixed powder of carbide ceramic and B4C; S4, the mixed powder obtained in S3 is pressed into a block and placed in a graphite crucible for three heat treatments to obtain (Ti 1 / 3 Zr 1 / 3Ta 1 / 3 )B y C z Boron carbide ceramic powder, prepared (Ti 1 / 3 Zr 1 / 3 Ta 1 / 3 )B y C z Boron carbide ceramic powder is a single-phase close-packed hexagonal crystal structure, in which: y+z=1, the five elements Ti, Zr, Ta, C, and B are evenly distributed.

2. The method for preparing a medium entropy boron carbide ceramic according to claim 1, characterized in that: In the S1, the molar ratio of TiO2, ZrO2, Ta2O5 and C in the raw material powder is 1:1:0.5:9.5; the particle size of each component is 1-3 μm, and the purity of each component is ≥99.9%.

3. The method for preparing a medium entropy boron carbide ceramic according to claim 2, characterized in that: The mass ratio of the raw material powder, zirconium oxide balls and anhydrous ethanol is 1:5:5; the ball milling time is 12 hours, the ball milling speed is 90 rpm; the drying temperature is 100° C., and the drying time is 2-3 hours.

4. The method for preparing a medium entropy boron carbide ceramic according to claim 1, characterized in that: In the above-mentioned S2, both the primary heat treatment and the secondary heat treatment are carried out in a vacuum sintering furnace, and the vacuum degree in the vacuum sintering furnace is less than 5 Pa; the temperature of the primary heat treatment is 1700°C, and the temperature of the secondary heat treatment is 2000°C.

5. The method for preparing a medium entropy boron carbide ceramic according to claim 4, characterized in that: The time of the primary heat treatment and the secondary heat treatment is 2 hours; after the heat treatment, the temperature is reduced to 1000°C at a rate of 10°C / min, and then naturally cooled to room temperature in the furnace.

6. The method for preparing a medium entropy boron carbide ceramic according to claim 1, characterized in that: In the S3, the mass ratio of carbide ceramic powder to B4C is 4:1; the ball milling time is 12 hours, and the ball milling speed is 90 rpm.

7. The method for preparing a medium entropy boron carbide ceramic according to claim 1, characterized in that: In the S4, the three heat treatments are carried out in a vacuum sintering furnace, the temperature of the three heat treatments is 2000°C, the time of the three heat treatments is 2h, and after the heat treatment, the temperature is reduced to 1000°C at a rate of 10°C / min, and then naturally cooled to room temperature in the furnace.

Citation Information

Patent Citations

  • Method of preparing ZrTiCB quaternary ceramic powder via combustion synthesis

    CN107827464A

  • High-entropy boron-containing carbide ultrahigh temperature ceramic powder and preparation method thereof

    CN109180188A